(untitled) (Research, Society and Development, 2020)
This review protocol aims to map and describe the scientific evidence on leprosy control actions according to the performance of the community health agent regarding the attributes of primary health care. The protocol was developed based on the guidelines of the Joanna Briggs Institute (JBI) and the methodology proposed by Arksey and O’Malley, in addition, it will meet the recommendations of the Preferred Reporting Items for Systematic and Meta-Analyzes - Extension for Scoping Reviews (PRISMA-ScR ). This protocol will guide the systematization of the development of the scoping review for the description and mapping of the panorama of the community agent’s performance in leprosy control actions evidenced in national and international literature.